Harmoni nilai persatuan indonesia dalam pancasila dan islam - MAULIDIYAH, SOFI (Maliki Interdisciplinary Journal, 2025)
This article discusses how the value of unity contained in Pancasila and Islamic teachings—two essential pillars in the national and religious life of Indonesia—work together harmoniously. The values of ukhuwah in Islam, such as ukhuwah wathaniyah (national brotherhood), ukhuwah basyariyah (human brotherhood), and ukhuwah islamiyah (brotherhood among Muslims), align with the Unity of Indonesia as reflected in the third principle of Pancasila. This article explores the harmony between the values of Pancasila and Islam, showing that the two mutually reinforce each other in forming a peaceful, tolerant, and united society, using a descriptive qualitative approach and literature study. The study finds that integrating Islamic values into the spirit of Pancasila strengthens national identity and reinforces the moral and spiritual foundations of Indonesia.